Effect of Ocean Iron Fertilization on the Phytoplankton Biological Carbon Pump (Advances in Applied Mathematics and Mechanics, 2011)
It has been proposed that photosynthetic plankton can be used as a biological carbon pump to absorb and sequester carbon dioxide in the ocean. In this paper, plankton population dynamicsare simulated in a single stratified water column to predict carbon dioxide sequestering due to surfaceiron fertilization in deep ocean. Using a predator-prey model and realistic parameter values,iron fertilization was found to only cause temporary blooms up to 5 months in duration, and relativelysmall increases in adsorption of atmospheric $\mathrm{CO_{2}}$.